Implicit and explicit measures of the sensory and hedonic analysis of beer: The role of tasting expertise. (February 2022) - Hinojosa-Aguayo, Irene; Garcia-Burgos, David; Catena, Andrés; González, Felisa
Graphical abstract: Highlights: The study compares explicit sensory and hedonic judgments with implicit EEG measures. Participants varied in their degree of beer tasting expertise. Groups' explicit judgments differed for body, astringency, and bitter persistence. Beer experts showed the largest number of explicit-implicit measures correlations. Correlations in experts mainly involved working and recognition memory components. Abstract: Measures of drinking and eating behaviors may be assessed both explicitly (e.g., sensory and quality judgments) and implicitly (e.g., Electroencephalography, EEG), although the relationship between the results of both approaches remains unclear and each might be differentially affected by acquired knowledge. The main aim of the present study was to determine the strength of the relationship between these measures in sensory and hedonic processing of beers depending on the degree of tasting expertise. Beer experts, experts in non-beer beverages or edibles, and non-expert consumers took part in a sensory analysis procedure where they rated beers in terms of their sensory attributes and general quality—visual, olfactory, and gustatory phases—as well as their global hedonic value while their brain activity was recorded. The results suggest that participants evaluated the sensory properties of the beers in a rather similar manner. However, during the gustatory phase, experts and general tasters differed in terms of the activation of brain areas related to memory processes, while general tasters and consumers differed in brain activation related to hedonic processing. The relationship between self-reported quality judgments and EEG activity — particularly in relation to recognition and working memory components — appeared to be stronger in experts in comparison with the other groups (lowest | r | = 0.67, p < .01). Although lower in number, significant relationships were also found in general tasters and consumers, primarily involving hedonic processing (lowest | r | = 0.58, p < .01) and recognition memory (lowest | r | = 0.57, p < .01) components. Moreover, those relationships differed significantly, mostly between experts and consumers (lowest | z | = 2.68, p < .01), in terms of the involvement of working memory components. Taken together, the results of this study suggest that beer experts have a more efficient pattern of gustatory processing and show a better fit between explicit (judgments) and implicit (EEG) measures of sensory and hedonic quality of beers.